The performance of HIV rapid antibody detection assays in children - Nuttall, James Jolyon Care (Department of Paediatrics and Child Health, 2016)
Background: HIV rapid antibody assays are important for screening children aged <18 months for HIV exposure and children ≥ 18 months for HIV infection. Limited available data indicate variable performance of different HIV rapid tests in comparison to laboratory HIV antibody assays. The aim of this study was to evaluate the diagnostic accuracy of 6 HIV rapid tests currently used in South Africa for screening children using whole blood. Methods: A prospective descriptive cross-sectional laboratory study was conducted at two paediatric healthcare facilities in South Africa. Sensitivity and specificity analyses and positive and negative likelihood ratios were performed. The reference standard was the laboratory HIV enzyme-linked immunosorbent assay (ELISA) test and HIV polymerase chain reaction (PCR) test. Results: Blood samples from 1159 children (896 <18 months of age) with valid HIV ELISA test results were included in the analysis. A total of 5768 HIV rapid tests (4446 in children <18 months of age) were performed. Sensitivity of HIV rapid tests for detecting HIV exposure among children <18 months of age ranged from 38.7% to 94.7%. Four HIV rapid tests attained specificity in excluding HIV exposure among children <18 months of age of >98%. Seroreversion rates were lowest with the Determine rapid test. Three HIV rapid tests (Abon, Advanced Quality, Determine) detected 100% of HIV-infected children <18 months of age, the Reveal, SD Bioline and Insti rapid tests missed 27 (41.5%), 1 (4.5%) and 1 (1.5%) of the HIV-infected children respectively. In children ≥ 18 months of age, sensitivity of rapid tests for detecting HIV infection ranged from 69.2% to 100% and specificity of all rapid tests was 100%. Conclusions: None of the 6 HIV rapid tests evaluated achieved both the World Health Organisation recommended sensitivity and specificity standards for any antibody assay used in screening for HIV exposure in children <18 months. The Determine test showed the best overall diagnostic accuracy and is therefore recommended as the preferred screening test for children. Recommendations: on the use of specific HIV rapid tests in infants and young children should be based on evaluation of their performance in the population to be tested.